Mental health promotion in France during the Covid19 pandemic. (20th October 2021) - Arwidson, P
Abstract: Public Health France have put in place a psychobehavioural surveillance system quickly after the beginning of the first lockdown in March 2020. Aside questions about people's perceptions about the pandemic (worry, perceived level of risk...), and their protective behaviours (social distancing, hand washing...), a module of questions on mental health (anxiety, depression and life satisfaction) was introduced. 22 rounds of this survey called CoviPrev have now been undertaken. This survey has been instrumental in raising the awareness by the government on the negative impacts of the pandemic on the mental health of the French population. We have designed, scientifically tested a media campaign to support the population's mental health. This campaign is now on air. This is the first national mental health media campaign since 2007. We hope it will initiate a long-term communication strategy aimed at promoting the mental health of the population.